1994
DOI: 10.2991/jnmp.1994.1.1.6
|View full text |Cite
|
Sign up to set email alerts
|

Symmetry reduction and exact solutions of the Navier-Stokes equations. I

Abstract: Ansatzes for the Navier-Stokes field are described. These ansatzes reduce the Navier-Stokes equations to system of differential equations in three, two, and one independent variables. The large sets of exact solutions of the Navier-Stokes equations are constructed.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
100
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(102 citation statements)
references
References 18 publications
2
100
0
Order By: Relevance
“…The case H = 0 corresponds to spherically symmetric flows. After substituting the representation (19) into the Navier-Stokes equations one has…”
Section: The Representation Of a Regular Partially Invariant Solution Ismentioning
confidence: 99%
See 2 more Smart Citations
“…The case H = 0 corresponds to spherically symmetric flows. After substituting the representation (19) into the Navier-Stokes equations one has…”
Section: The Representation Of a Regular Partially Invariant Solution Ismentioning
confidence: 99%
“…Several articles [11][12][13][14][15][16][17][18][19][20][21] are devoted to invariant solutions of the Navier-Stokes equations. 3 While partially invariant solutions of the Navier-Stokes equations have been less studied, 4 there has been substantial progress in studying such classes of solutions of inviscid gas dynamics equations [1,3,6,[22][23][24][25][26][27].…”
Section: The Navier-stokes Equationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Classification of infinite-dimensional subalgebras of this algebra was studied in [6]. 3 Short reviews devoted to invariant solutions of the Navier-Stokes equations can be found in [14][15][16]. 4 Firstly the approach of partially invariant solutions to the NavierStokes equations was applied in [17].…”
Section: The Reduction Of the Navier-stokes Equationsmentioning
confidence: 99%
“…Given any subgroup of the symmetry group, one can write down the equations for the similarity solution with respect to this subgroup. This reduced system is of fewer variables and easier to solve generally [1,2,3,4,5]. But a Lie group (or Lie algebra) usually contains infinitely many subgroups (or subalgebras) of the same dimension, it is not usually feasible to list all possible similarity solutions.…”
Section: Introductionmentioning
confidence: 99%